Physical and Mental Health, Anxiety and Depressive Symptoms in Caregivers of Patients in Vegetative State and Minimally Conscious State. (27th May 2013) - Pagani, M.; Giovannetti, A. M.; Covelli, V.; Sattin, D.; Raggi, A.; Leonardi, M.
<x xml:space="preserve">Abstract</x> Caregivers of patients in vegetative state and minimally conscious state play a crucial role in the process of taking care and, as previous studies reported, they can suffer of high burden and negative health outcomes. The aim of this national cross‐sectional study was to assess whether physical and mental health of caregivers, considering gender differences, is related to the presence of depressive symptoms, anxiety, age and patient's disease duration. Four‐hundred and eighteen caregivers, 294 women and 124 men, completed the State Trait Anxiety Inventory‐Y, Beck Depression Inventory, second version and Short Form‐12. Hierarchical multiple regression analyses were performed to evaluate to which extent depressive and anxiety symptoms predict physical and mental health. Men reported higher levels of mental health state, whereas physical health was not different across gender. High levels of anxiety symptoms were associated to negative mental health outcomes in both genders, whereas depressive symptoms were found to impact on female's mental and physical health only. A comprehensive and cost‐effective screening of anxiety and depressive symptoms may help to identify determinants of health worsening in order to plan, when necessary, caregivers' support. Copyright © 2013 John Wiley & Sons, Ltd. Key Practitioner Messages Female caregivers of patients in vegetative state and minimally conscious state have poorer levels of mental health, whereas physical health is similar to men's. Anxiety symptoms are related to negative mental health outcomes in both male and female caregivers, whereas depressive symptoms are found to impact on female mental and physical health only. It is essential to consider and assess depressive and anxiety symptoms as they may contribute to caregivers' health worsening. This knowledge can lead to plan more comprehensive and tailored caregivers' supports and a better care for patients.